2021
DOI: 10.3389/fgene.2021.700636
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Markers Are Associated With Differences in Isocyanate Biomarker Levels in Exposed Spray-Painters

Abstract: Isocyanates are respiratory and skin sensitizers that are one of the main causes of occupational asthma globally. Genetic and epigenetic markers are associated with isocyanate-induced asthma and, before asthma develops, we have shown that genetic polymorphisms are associated with variation in plasma and urine biomarker levels in exposed workers. Inter-individual epigenetic variance may also have a significant role in the observed biomarker variability following isocyanate exposure. Therefore, we determined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 87 publications
(119 reference statements)
0
4
0
Order By: Relevance
“…In line with this, several EWAS have also linked CpG methylation to environmental exposures, e.g. air quality 23 , stress 24 , occupational exposure to chemicals 25,26 , prescribed medications 27 , dietary habits such as coffee and alcohol consumption 28,29 and supplement intake 30 .…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…In line with this, several EWAS have also linked CpG methylation to environmental exposures, e.g. air quality 23 , stress 24 , occupational exposure to chemicals 25,26 , prescribed medications 27 , dietary habits such as coffee and alcohol consumption 28,29 and supplement intake 30 .…”
Section: Introductionmentioning
confidence: 82%
“…, occupational exposure to chemicals 25,26 , prescribed medications 27 , dietary habits such as coffee and alcohol consumption 28,29 and supplement intake 30 .…”
mentioning
confidence: 99%
“…Given the limited half-life of IgE antibodies, limited temporal presence of IgG antibodies after exposure, and variability in individual responses, reliance on antibodies as markers of exposure or disease may not be feasible [ 28 ]. While advancements in urinalysis and epigenome sequencing may provide future means of performing routine isocyanate exposure monitoring, no such method is currently widely available [ 40 , 41 ]. Difficulties in monitoring occupational exposure necessitate undertaking efforts to minimize isocyanate exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of HDI bound was quantified with HDA released after strong acidic hydrolysis. To date, all methods to quantify albumin adducts were performed with an immunological assay ,, or with chemical hydrolysis, followed by GC–mass spectrometry (MS) analysis. For in vitro modified albumin, Wisnewski et al demonstrated a linear relationship between the immunological test and the chemical hydrolysis that releases HDA. Lysine adducts present in albumin modified in vitro with HDI appear to be crucial for the immunological response of antibodies present in exposed workers .…”
Section: Introductionmentioning
confidence: 99%